2020
DOI: 10.1186/s12889-020-09203-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting return to work after long-term sickness absence with subjective health complaints: a prospective cohort study

Abstract: Background: Long-term sickness absence results in increased risks of permanent disability and a compromised quality of life. Return to work is an important factor in reducing these risks. Little is known about return to work factors for long-term sick-listed workers with subjective health complaints. The aim of this study was to evaluate prognostic factors for partial or full return to a paid job for at least 28 days for long-term sick-listed workers with subjective health complaints, and to compare these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition to the economic cost, being out of the workplace due to disability has major psychosocial costs for the individual, causing reduced social capital, sense of purpose, quality of life, and standard of living 5,6 . Return to work—referring to a return to paid employment in the form of a previous job, a previous job in modified form, or a new job, including either part-time or full-time work 7 following illness or injury—is an important factor in reducing these economic, social, and personal consequences 8 . Indeed, returning to work can “enhance recovery, self-esteem, confidence, social identity and overall quality of life.” 9 (p.953) Its importance is such that the need to promote vocational rehabilitation (which has been defined as a process where those disadvantaged by illness or disability are enabled to access, maintain, or return to employment or other useful occupation) 2 is enshrined in the United Nations Convention on the Rights of Persons with Disabilities 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the economic cost, being out of the workplace due to disability has major psychosocial costs for the individual, causing reduced social capital, sense of purpose, quality of life, and standard of living 5,6 . Return to work—referring to a return to paid employment in the form of a previous job, a previous job in modified form, or a new job, including either part-time or full-time work 7 following illness or injury—is an important factor in reducing these economic, social, and personal consequences 8 . Indeed, returning to work can “enhance recovery, self-esteem, confidence, social identity and overall quality of life.” 9 (p.953) Its importance is such that the need to promote vocational rehabilitation (which has been defined as a process where those disadvantaged by illness or disability are enabled to access, maintain, or return to employment or other useful occupation) 2 is enshrined in the United Nations Convention on the Rights of Persons with Disabilities 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Most research on workers with SHC has focused on identifying which workers are at increased risk of sickness absence, and on finding ways for absent workers to return to work [ 7 , 8 , 9 ]. This research has revealed that psychosocial and work-related factors in particular, such as mental distress, self-perceived disability, self-efficacy and expectations, social support, work demands, and compensation status, are associated with sickness absence and possibilities for returning to work [ 7 , 8 , 9 ]. Many researchers have argued that modification of these factors may help to prevent sickness absence and to support full return to work [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Better func tional recovery is associated with work participation after stroke (11), critical illness (12) and with inflammatory joint conditions (13). However, additional factors, such as coping, expectation of recovery, and duration of absence, have also been found to predict work participation (14)(15)(16)(17).…”
mentioning
confidence: 99%